Genetic Interactions Between Aspergillus fumigatus Basic Leucine Zipper (bZIP) Transcription Factors AtfA, AtfB, AtfC, and AtfD - Silva, Lilian Pereira; Horta, Maria Augusta Crivelente; Goldman, Gustavo Henrique (Frontiers in Fungal Biology, 2021)
Aspergillus fumigatus is an opportunistic fungus, capable of causing Invasive Aspergillosis in immunocompromised patients, recently transplanted or undergoing chemotherapy. In the present work, we continued the investigation on A. fumigatus AtfA-D transcription factors (TFs) characterizing possible genetic and physical interactions between them after normal growth and stressing conditions. We constructed double null mutants for all the possible combinations of ∆atfA-, -B, -C, and –D, and look into their susceptibility to different stressing conditions. Our results indicate complex genetic interactions among these TFs that could impact the response to different kinds of stressful conditions. AtfA-D interactions also affect the A. fumigatus virulence in Galleria mellonella. AtfA:GFP is approximately 97% located in the nucleus while about 20 to 30% of AtfB, -C, and -D:GFP locate into the nucleus in the absence of any stress. Under stressing conditions, AtfB, -C, and -D:GFP translocate to the nucleus about 60 to 80 % upon the addition of sorbitol or H2O2. These four TFs are also interacting physically forming all the possible combinations of heterodimers. We also identified that AtfA-D physically interact with the MAPK SakA in the absence of any stress and upon osmotic and cell wall stresses. They are involved in the accumulation of trehalose, glycogen and metabolic assimilation of different carbon sources.